Neural Entrainment to Rhythmically Presented Auditory, Visual, and Audio-Visual Speech in Children - Power, Alan J.; Mead, Natasha; Barnes, Lisa; Goswami, Usha (Frontiers in Psychology, 2012)
Auditory cortical oscillations have been proposed to play an important role in speech perception. It is suggested that the brain may take temporal ‘samples’ of information from the speech stream at different rates, phase-resetting ongoing oscillations so that they are aligned with similar frequency bands in the input (‘phase locking’). Information from these frequency bands is then bound together for speech perception. To date, there are no explorations of neural phase-locking and entrainment to speech input in children. However, it is clear from studies of language acquisition that infants use both visual speech information and auditory speech information in learning. In order to study neural entrainment to speech in typically-developing children, we use a rhythmic entrainment paradigm (underlying 2 Hz or delta rate) based on repetition of the syllable “ba”, presented in either the auditory modality alone, the visual modality alone, or as auditory-visual speech (via a “talking head”). To ensure attention to the task, children aged 13 years were asked to press a button as fast as possible when the “ba” stimulus violated the rhythm for each stream type. Rhythmic violation depended on delaying the occurrence of a “ba” in the isochronous stream. Neural entrainment was demonstrated for all stream types, and individual differences in standardized measures of language processing were related to auditory entrainment at the theta rate. Further, there was significant modulation of the preferred phase of auditory entrainment in the theta band when visual speech cues were present, indicating cross-modal phase resetting. The rhythmic entrainment paradigm developed here offers a method for exploring individual differences in oscillatory phase locking during development. In particular, a method for assessing neural entrainment and cross-modal phase resetting would be useful for exploring developmental learning difficulties thought to involve temporal sampling, such as dyslexia.